Passive fuel delivery and efficient anoxic condition in anode improve performance of methanol biofuel cell. (1st January 2022) - Das, Priyanki; Bachu, Vinay; Barbora, Lepakshi; Dutta, Arup; Sarma, Mrinal Kumar; Goswami, Pranab
Graphical abstract: Highlights: An enzymatic biofuel cell with passive delivery system for methanol fuel developed. The control fuel delivery with sealing O2 contact to anode improved the performance. A record operational stability and coulombic efficiency gained with the stacked cells. The high stability and efficiency greatly contributed to its scope of applications. Abstract: The operational stability, power efficiency, and technical simplicity of enzymatic biofuel cells are the focus area of research for practical applications of this green energy-generating device. Here, we report some critical findings on these issues on a methanol-fuelled pure biofuel cell fabricated by using alcohol oxidase and bilirubin oxidase as anodic and cathodic catalysts, respectively. The cell was fabricated with a new design strategy comprising efficient anoxic condition in the anodic chamber, adequate airflow to the cathode for enhancing oxygen reduction reactions, and a passive fuel pumping facility to the anode. A magnetic nanoparticle-based bio-nanocomposite matrix on the carbon-cloth electrode offered as a biocompatible enzyme immobilization matrix for harvesting electrons in the cell through the direct electron transfer mechanism as validated by cyclic voltammetry. Six units of the cells, when connected in a series, the device's potential increased to 4.3-fold (3.1 V) and rested at a stable state under a load with a half-life of ∼ 372 days and a coulombic efficiency of 60%. This high operational stability has been attributed to the efficient anoxic setup in the anodic chamber that supported the stability of alcohol oxidase, the activity of which was intact even after 49 days of the operation. This work also demonstrated that the prolonged interaction of molecular oxygen with the oxidase drastically inactivates it without affecting the structural integrity of the enzyme protein. This enzymatic fuel cell with improved design and functions is a step forward for achieving practical application as a standalone power supply to small-scale devices.